2003
DOI: 10.1111/j.1365-3083.2003.01340.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Features of Peripheral Blood Leucocytes During Early Stages of Human Infection with Trypanosoma cruzi

Abstract: We performed a cross-sectional flow cytometric analysis of peripheral blood mononuclear cells to evaluate human immunologic status during early stages of Trypanosoma cruzi infection in children. We identified major immunological features corresponding to three proposed phases of disease: early acute (EA) phase, late acute (LA) phase and recent chronic (RC) phase. EA phase was accompanied by expansion of conventional B cells, up-regulation of CD54 on monocytes and down-regulation of CD54 on T cells and not asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 25 publications
4
29
0
3
Order By: Relevance
“…Despite several reports of higher T-cell activation during chronic Chagas disease [14e16], we have previously demonstrated that E-IND is characterized by a T-cell-independent immunity with no changes in the frequency of circulating HLA-DR þ T-cells [17]. Because HLA-DR is commonly referred to as a late-stage activation cell surface marker, we have further focused the T-cell activation issue by characterizing the expression of an early activation marker, CD69, aiming to evaluate the T-cell activation profile before and after the Bz-treatment.…”
Section: 1mentioning
confidence: 99%
“…Despite several reports of higher T-cell activation during chronic Chagas disease [14e16], we have previously demonstrated that E-IND is characterized by a T-cell-independent immunity with no changes in the frequency of circulating HLA-DR þ T-cells [17]. Because HLA-DR is commonly referred to as a late-stage activation cell surface marker, we have further focused the T-cell activation issue by characterizing the expression of an early activation marker, CD69, aiming to evaluate the T-cell activation profile before and after the Bz-treatment.…”
Section: 1mentioning
confidence: 99%
“…An increase in the frequency of circulating B cell seems to occur during the late acute phase of T. cruzi infection in humans, but only becoming significant at the beginning of the chronic phase (100). Nonetheless, it has been proposed that, in patients with established chronic Chagas disease, the number of CD19 + cells is not different from that of non-infected individuals (101, 102), suggesting a subsequent contraction of this population.…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…With the aim of contributing to this field of investigation, studies have been developed to characterise immunological biomarkers in patients presenting distinct clinical manifestations of the disease (Reis et al 1993, Dutra et al 1994, 1996, Lemos et al 1998, Gomes et al 2003, Sathler-Avelar et al 2003, Souza et al 2004, Vitelli-Avelar et al 2005, 2006, 2008. Additionally, other investigators have also focused on what impact etiological treatment with benznidazole (Bz) may have on the anti-T. cruzi immune response (Bahia-Oliveira et al 2000, Sathler-Avelar et al 2006, 2008, Vitelli-Avelar et al 2008.…”
mentioning
confidence: 99%